Thermo-regulated adhesion of the Streptococcus thermophilus Δrgg0182 strain - Francius, Grégory (Langmuir : the ACS journal of surfaces and colloids, 2013)
The physicochemical determinants governing the temperature-dependent adhesion of Streptococcus thermophilus to abiotic surfaces are identified under physiological condition for cells either lacking or not the Rgg0182 transcriptional regulator involved in their thermal adaptation. For that purpose, the wild type LMG18311 strain and Δrgg0182 mutant were imaged using highly resolved atomic force microscopy (AFM) at various cell growth temperatures (42 to 55 °C). The corresponding hydrophobic/hydrophilic balance of the cells was quantitatively addressed via the measurement by chemical force microcopy of their adhesion to a reference hydrophobic surface. Analysis of force-separation distance curves further allowed us to discriminate cell surfaces according to the presence or absence of biopolymers. These results were interpreted in relation to the measured adhesion of the Δrgg0182 mutant onto the hydrophobic wall of microwells in the temperature range from 46 to 52 °C. It is evidenced that the viscoelastic Δrgg0182 cell envelop behaves as a thermo-responsive film whose hydrophobicity increases with increasing temperature, thereby favoring cell attachment to hydrophobic surfaces. Regardless cell growth temperature, wild-type cells do not attach to hydrophobic surfaces and the presence of the Rgg0182 transcriptional regulator is associated with the synthesis of hydrophilic cell surface biopolymers. Throughout, the impact of electrostatics on bioadhesion is ruled out upon examination of electrohydrodynamic cell properties at 50 °C